2014
DOI: 10.1371/journal.pone.0092779
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Nodal Involvement in Primary Rectal Carcinoma without Invasion to Pelvic Structures: Accuracy of Preoperative CT, MR, and DWIBS Assessments Relative to Histopathologic Findings

Abstract: ObjectiveTo investigate the accuracy of preoperative computed tomography (CT), magnetic resonance (MR) imaging and diffusion-weighted imaging with background body signal suppression (DWIBS) in the prediction of nodal involvement in primary rectal carcinoma patients in the absence of tumor invasion into pelvic structures.Methods and MaterialsFifty-two subjects with primary rectal cancer were preoperatively assessed by CT and MRI at 1.5 T with a phased-array coil. Preoperative lymph node staging with imaging mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…It is difficult for radiologists to make correct and timely judgements based on all the factors above in a short period of time, especially when they are faced with a large number of cases. Therefore, different radiologists can reach different conclusions from the same MRI image; in particular, it is difficult to obtain an accurate and objective evaluation of lymph node metastasis (2)(3)(4)(5). Currently, the diagnostic criteria for metastatic lymph nodes are not identical, and lymph node size is taken as the diagnostic criteria in most cases; however, there has been no agreed-upon conclusion on the size threshold for metastatic lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult for radiologists to make correct and timely judgements based on all the factors above in a short period of time, especially when they are faced with a large number of cases. Therefore, different radiologists can reach different conclusions from the same MRI image; in particular, it is difficult to obtain an accurate and objective evaluation of lymph node metastasis (2)(3)(4)(5). Currently, the diagnostic criteria for metastatic lymph nodes are not identical, and lymph node size is taken as the diagnostic criteria in most cases; however, there has been no agreed-upon conclusion on the size threshold for metastatic lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Roy et al reported no significant difference between the median ADC value of metastatic LNs and non-metastatic LNs in the pelvic LNs of gynecological malignancies [ 48 ]. Additionally, Zhou et al reported that the sensitivity and negative predictive values for DWI were 100%, with an accuracy for DWI of only 40.4%, and they argued that DWI is currently unlikely to be useful in clinical practice due to its low accuracy [ 49 ]. There still remains controversy, and further investigation is needed regarding the application of the DWI and ADC values for discriminating between metastatic and benign lymph nodes, including LPLNs of advanced rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Prediction of nodal staging in patients with primary rectal carcinoma is important for prognosis, and preoperative assessment of lymph node involvement has important value in developing the therapeutic schedule and a new auxiliary treatment (22). CT criteria for metastatic lymph nodes included size, border, shape and enhancement.…”
Section: Discussionmentioning
confidence: 99%